Preparation process of high-compaction polyanionic positive electrode material

By performing secondary grinding and high-temperature secondary sintering on the polyanionic positive electrode material, and modifying it with high-conductivity graphitized inorganic carbon, the problems of material compaction density and low electronic conductivity are solved, and the material performance is significantly improved.

CN119551644APending Publication Date: 2025-03-04ZIGONG JIA SODIUM NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411603378.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the sintering process, the existing polyanionic positive electrode materials contain easily decomposed components, resulting in a large number of pores in the finished product, resulting in a low compaction density of the material and affecting the electronic conductivity.

Method used

The high-compression preparation process is adopted to perform secondary grinding of the material after primary sintering to destroy the pore structure inside the particles, and to modify it using high-conductivity graphitized inorganic carbon during the secondary sintering to improve the compaction density and electronic conductivity of the material.

Benefits of technology

It significantly improves the compaction density and electronic conductivity of the material, improves the rate performance and cycle stability of the material, and improves the yield rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551644A_ABST
    Figure CN119551644A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-compaction polyanionic positive electrode material. The preparation process comprises the following steps: S1, mixing raw material slurry: mixing and grinding a sodium source, a transition metal source, an anion source, a first carbon source and a dispersing agent by a wet method; s2, the raw material powder is dried, specifically, drying is conducted, solid-liquid separation is achieved, and dried raw material powder is obtained; s3, high-temperature calcination of the porous polyanion material: carrying out high-temperature calcination in a protective atmosphere, and naturally cooling after nucleation crystallization; s4, mixing precursor slurry: mixing and grinding a porous polyanion material and a second carbon source by a wet method; s5, precursor powder drying: drying the material to realize solid-liquid separation so as to obtain dry and compact precursor powder; and S6, high-temperature secondary sintering: carrying out high-temperature secondary sintering in a protective atmosphere, and naturally cooling to obtain the high-compaction polyanion material. The method has the characteristics of high compaction density, high electronic conductivity and high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a preparation process of a high-density polyanion positive electrode material. Background Art

[0002] There are many types of positive electrode materials for sodium-ion batteries, including Prussian blue and its analogs, transition metal oxides, and polyanionic materials. Among them, Prussian blue and its analogs have high capacity and discharge voltage, but the lattice water in their structure is difficult to remove, and the charge and discharge process is prone to gasification, causing battery failure; transition metal oxides have a high compaction density and a high discharge capacity, but there are complex phase changes in the process of sodium insertion and deintercalation, which leads to structural collapse and serious performance degradation; polyanionic compounds have a stable three-dimensional framework, excellent rate performance, and high stability, but their capacity is low and the compaction density is small, which is only suitable for energy storage fields that do not require high energy density.

[0003] Polyanionic materials are framework structures composed of alkali metal ions, transition metal ions and anion groups connected in the form of common points / surfaces / lines. At present, the solid phase method is often used to prepare this material on the market. The process is to mix and grind the sodium source, transition metal source, anion source and carbon source, dry and sinter to obtain the final material.

[0004] However, the materials prepared by this process contain a large number of easily decomposed components in the raw materials during the sintering process, resulting in a large number of pores in the final product, resulting in a low compaction density of the material. At the same time, the presence of pores will also have a serious impact on the electronic conductivity inside the particles, which is not conducive to the improvement of the material's rate performance. Based on this, the development of high-density, high-conductivity polyanion materials is crucial for the development of the sodium battery industry. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of a high-density polyanion positive electrode material, which has the characteristics of high compaction density, high electronic conductivity and high yield.

[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: wet-mixing and grinding the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry; S2. Drying the raw material powder: drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder; S3. High-temperature calcination of porous polyanion materials: in a protective atmosphere, the precursor powder is calcined at high temperature to remove volatile components, and the porous polyanion material is obtained by naturally cooling after nucleation and crystallization; S4, mixing the precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry; S5. Drying the precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder; S6. High-temperature secondary sintering: In a protective atmosphere, the dense precursor powder is subjected to high-temperature secondary sintering to further shrink the particles, and a highly compacted polyanion material is obtained after natural cooling.

[0007] In the present invention, the electronic conductivity and compaction density of the material are regulated by a secondary sintering process, which is mainly achieved by re-modifying the particle morphology and adjusting the particle porosity to achieve mutual interlocking between materials, thereby achieving an increase in compaction density and electronic conductivity. The preparation process is to mix and grind the sodium source, transition metal source, anion source, and carbon source evenly, and then dry to achieve solid-liquid separation, and obtain a porous polyanion material after sintering. After that, the porous polyanion material is ground again and mixed with inorganic high-conductivity carbon. The shear force of the grinding process destroys the pores inside the material, and at the same time, the inorganic carbon is attached and modified on the surface of the material. Finally, after drying and secondary sintering, a high-conductivity, high-density polyanion material can be obtained.

[0008] Furthermore, in step S1, the first carbon source is one or more of citric acid, tartaric acid, ascorbic acid, acrylic acid, glucose, sucrose, starch, lactose, maltose, cyclodextrin, cellulose and their derivatives.

[0009] Furthermore, in step S4, the second carbon source is one or more of the inorganic carbon-containing compounds carbon nanotubes, carbon fibers, carbon black, graphene, and flake graphite; its purpose is to construct an electronic conductive network on the surface of the material during the secondary sintering process, improve the electron transmission capacity, and reduce the internal resistance. At the same time, this type of carbon material does not shrink or produce gas during the secondary sintering process, and there is no pore formation phenomenon, which is conducive to the realization of densification and high-compacted materials.

[0010] Further, in steps S3 and S6, the sintering temperature of high-temperature calcination and high-temperature secondary sintering is 450-800°C, and the time is 0.1-24H. When the temperature is lower than 450°C or the time is lower than 0.1H, the volatile components in the material cannot be completely decomposed and removed, and at the same time, the melting and crystallization degree of the material at this temperature is insufficient, the crystal form is incomplete, and the pyrolysis degree of the surface carbon layer is low, the electronic conductivity and ion conductivity are low, and the material performance is poor. When the temperature is higher than 800°C, the melting of the material is intensified, the structural stability is reduced, and it is easy to decompose to form impurities such as oxides and phosphides that are more thermodynamically stable; when the sintering time exceeds 24H, the energy consumption increases, and there is no obvious improvement in the crystal form and phase purity of the material.

[0011] Furthermore, in steps S3 and S6, the protective atmosphere is a non-oxidizing atmosphere, which is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium; its purpose is to prevent the oxidation of transition metals in the material during sintering and to avoid oxidative decomposition of the carbon layer on the surface of the material.

[0012] Further, in step S1, the dispersant is one or more of acrylic acid (ester) / acrylamide copolymers and their derivatives, styrene / acrylic acid (ester) copolymers and their derivatives, maleic acid (ester) / acrylic acid (ester) copolymers and their derivatives, maleic anhydride / styrene copolymers and their derivatives, maleic anhydride / α-olefin copolymers and their derivatives, maleic acid or its sodium salt / polyol allyl monoether polymers and their derivatives; its mechanism of action is that the hydrophobic hydrocarbon group is attached to the surface of the solid particles, hindering the mutual agglomeration between the particles, while the water-absorbing hydroxyl, carboxyl, etc. are dissolved in water, so that the solid particles are evenly suspended in the solution, thereby improving the stability and uniformity of the slurry.

[0013] Furthermore, in steps S1 and S4, the grinding method is sand milling and / or ball milling, and the purpose of pulverizing and dispersing the material particles is achieved in the form of mechanical force and shear force; its action mechanism is that the high-speed impact of the grinding medium will produce strong shear force, and when this force acts on the solid material, it will cause cracking, falling, pulverization and other phenomena at the solid interface. After a long period of grinding, the solid particles will be broken to the nm level and evenly dispersed in the slurry.

[0014] Furthermore, in steps S2 and S5, the drying method is one or more of flash drying, spray drying, high temperature cracking drying, freeze drying, air drying, and heating evaporation; the purpose is to achieve solid-liquid separation and obtain dry precursor powder, which is convenient for subsequent high temperature calcination of the powder.

[0015] Further, in step S1, the sodium source is an inorganic sodium source and / or an organic sodium source, the inorganic sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium nitrate, and sodium oxalate; the organic sodium source is one or more of sodium formate, sodium acetate, sodium propionate, sodium phenol, sodium ethanol, sodium ascorbate, sodium citrate, sodium gluconate, ethylenediaminetetraacetic acid and their derivatives.

[0016] Further, in step S1, the transition metal source is one or more of a manganese source, a cobalt source, and an iron source; the manganese source is one or more of manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese element and its oxide, basic manganese oxide, manganese acetate, and manganese phosphate; the cobalt source is one or more of cobalt nitrate, cobalt sulfate, cobalt hydroxide, cobalt element and its oxide, cobalt oxalate, cobalt carbonate, cobalt acetate, and cobalt phosphate; the iron source is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferric formate, ferric acetate, ferric hydroxide / ferrous hydroxide, ferrous oxalate, ferric phosphate, iron element and its oxide.

[0017] Further, in step S1, the anion source is an inorganic phosphorus source and / or an organic phosphorus source, the inorganic phosphorus source is one or more of phosphoric acid, sodium phosphate and its acid salts, ammonium phosphate and its acid salts, pyrophosphoric acid, sodium pyrophosphate and its acid salts, ammonium pyrophosphate and its acid salts, metaphosphoric acid, sodium metaphosphate and its acid salts, and sodium polyphosphate; the organic phosphorus source is one or more of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, diethylenetriamine penta (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, polyaminopolyether methylene phosphonic acid, 2-hydroxyphosphonoacetic acid, polyol phosphate, and di-1,6-hexamethylene triamine penta (methylene phosphonic acid).

[0018] The present invention provides a process for preparing a high-density polyanion positive electrode material, which has the following beneficial effects: First, the compaction density is high. When preparing polyanion materials by traditional liquid phase method or solid phase method, the sodium source, transition metal source, anion source and carbon source are often mixed evenly and then spray dried, and then sintered in one step to obtain the final material. However, in this process, the easily decomposable components in the raw materials decompose in large quantities at high temperatures, generating a large amount of gas, causing a large number of holes to be generated inside the material particles, the powder becomes polished, and the compaction density is greatly reduced. The present invention grinds the material after the first sintering for a second time to destroy the internal pore structure of the material particles, so that the particles are re-stacked and distributed. During the secondary sintering process, due to the absence of decomposition components, the density of the prepared material is increased and the compaction density is improved.

[0019] Second, high electronic conductivity. Traditional polyanion materials sintered once contain a large number of pores inside the particles, which leads to a decrease in the number of electron transmission sites between particles and an increase in internal resistance. The crushing of the primary sintered particles in the secondary sintering process effectively reduces the pores inside the particles. At the same time, through further modification of high-conductivity graphitized inorganic carbon, the number of electron transmission sites inside the particles is greatly increased, the internal resistance of the material interface is reduced, and the material rate performance is improved.

[0020] Third, the yield rate is high. Polyanion materials have extremely high requirements for the uniformity of ions in the precursor slurry. Local uneven ion concentrations can easily lead to phase separation in the finished product. The secondary sintering process can avoid this problem. When there are impurities in the product after the first sintering, the heterogeneity of the elements in the material can be identified through elemental analysis or phase analysis. Additional supplementation can be used in the secondary sanding process to achieve the reconstruction of the phase after the secondary sintering and improve the yield rate of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The high-density Na4Fe 2.91 (PO4)2P2O7 material SEM; Figure 2 The porous Na4Fe 2.91 SEM of (PO4)2P2O7 material. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0023] The present invention discloses a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: wet-mixing and grinding the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry; S2. Drying the raw material powder: drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder; S3. High-temperature calcination of porous polyanion materials: in a protective atmosphere, the precursor powder is calcined at a high temperature, and after nucleation and crystallization, the porous polyanion material is obtained by naturally cooling down; S4, mixing the precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry; S5. Drying the precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder; S6. High-temperature secondary sintering: In a protective atmosphere, the dense precursor powder is subjected to high-temperature secondary sintering, and a high-density polyanion material is obtained after natural cooling.

[0024] Furthermore, in step S1, the first carbon source is one or more of citric acid, tartaric acid, ascorbic acid, acrylic acid, glucose, sucrose, starch, lactose, maltose, cyclodextrin, cellulose and their derivatives.

[0025] Furthermore, in step S4, the second carbon source is one or more of inorganic carbon-containing compounds such as carbon nanotubes, carbon fibers, carbon black, graphene, and flake graphite.

[0026] Furthermore, in steps S3 and S6, the sintering temperature of the high-temperature calcination and the high-temperature secondary sintering is 450-800° C., and the time is 0.1-24 hours.

[0027] Furthermore, in steps S3 and S6, the protective atmosphere is a non-oxidizing atmosphere, which is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium.

[0028] Furthermore, in step S1, the dispersant is one or more of acrylic acid (ester) / acrylamide copolymers and their derivatives, styrene / acrylic acid (ester) copolymers and their derivatives, maleic acid (ester) / acrylic acid (ester) copolymers and their derivatives, maleic anhydride / styrene copolymers and their derivatives, maleic anhydride / α-olefin copolymers and their derivatives, maleic acid or its sodium salt / polyol allyl monoether polymers and their derivatives.

[0029] Furthermore, in steps S1 and S4, the grinding method is sand milling and / or ball milling.

[0030] Furthermore, in steps S2 and S5, the drying method is one or more of flash drying, spray drying, high temperature cracking drying, freeze drying, air drying, and heating evaporation.

[0031] Further, in step S1, the sodium source is an inorganic sodium source and / or an organic sodium source, the inorganic sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium nitrate, and sodium oxalate; the organic sodium source is one or more of sodium formate, sodium acetate, sodium propionate, sodium phenol, sodium ethanol, sodium ascorbate, sodium citrate, sodium gluconate, ethylenediaminetetraacetic acid and their derivatives.

[0032] Further, in step S1, the transition metal source is one or more of a manganese source, a cobalt source, and an iron source; the manganese source is one or more of manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese element and its oxide, basic manganese oxide, manganese acetate, and manganese phosphate; the cobalt source is one or more of cobalt nitrate, cobalt sulfate, cobalt hydroxide, cobalt element and its oxide, cobalt oxalate, cobalt carbonate, cobalt acetate, and cobalt phosphate; the iron source is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferric formate, ferric acetate, ferric hydroxide / ferrous hydroxide, ferrous oxalate, ferric phosphate, iron element and its oxide.

[0033] Further, in step S1, the anion source is an inorganic phosphorus source and / or an organic phosphorus source, the inorganic phosphorus source is one or more of phosphoric acid, sodium phosphate and its acid salts, ammonium phosphate and its acid salts, pyrophosphoric acid, sodium pyrophosphate and its acid salts, ammonium pyrophosphate and its acid salts, metaphosphoric acid, sodium metaphosphate and its acid salts, and sodium polyphosphate; the organic phosphorus source is one or more of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, diethylenetriamine penta (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, polyaminopolyether methylene phosphonic acid, 2-hydroxyphosphonoacetic acid, polyol phosphate, and di-1,6-hexamethylene triamine penta (methylene phosphonic acid).

[0034] Example 1 This embodiment relates to a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: Wet-mix and grind the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry. Specifically, the first carbon source is citric acid, tartaric acid, ascorbic acid, cyclodextrin, cellulose and its derivatives; the dispersant is maleic anhydride / styrene copolymer and its derivatives, maleic anhydride / α-olefin copolymer and its derivatives, maleic acid or its sodium salt / polyol allyl monoether polymer and its derivatives; the grinding method is sand milling and ball milling; the sodium source is an inorganic sodium source and an organic sodium source, the inorganic sodium source is sodium carbonate, sodium bicarbonate, sodium hydroxide, and the organic sodium source is sodium formate, acetic acid The transition metal sources are manganese source and iron source; the manganese source is manganese oxalate, basic manganese oxide, manganese acetate, and manganese phosphate; the iron source is ferric sulfate, ferrous sulfate, ferric nitrate, and ferric formate; the anion source is an inorganic phosphorus source and an organic phosphorus source, the inorganic phosphorus source is phosphoric acid, sodium phosphate and its acid salts, ammonium phosphate and its acid salts, and the organic phosphorus source is hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, and diethylenetriamine penta (methylene phosphonic acid).

[0035] S2. Drying of raw material powder: Drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder. Specifically, the drying method is flash freeze drying or forced air drying.

[0036] S3, high temperature calcination of porous polyanion material: in a protective atmosphere, the precursor powder is calcined at high temperature, and after nucleation and crystallization, the porous polyanion material is obtained by natural cooling. Specifically, the sintering temperature is 550°C, the time is 20 hours, and the protective atmosphere is a non-oxidizing atmosphere, which is nitrogen, hydrogen, or helium.

[0037] S4, mixing of precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry. Specifically, the second carbon source is an inorganic carbon-containing compound carbon nanotube or flake graphite; the grinding method is sand milling and ball milling.

[0038] S5, drying of precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder. Specifically, the drying method is spray drying.

[0039] S6, high temperature secondary sintering: in a protective atmosphere, the dense precursor powder is subjected to high temperature secondary sintering, and a high-density polyanion material is obtained after natural cooling. Specifically, the sintering temperature is 700°C, the time is 4 hours, and the protective atmosphere is a non-oxidizing atmosphere, which is nitrogen or argon.

[0040] Example 2 This embodiment relates to a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: Wet-mix and grind the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry. Specifically, the first carbon source is citric acid, tartaric acid, and ascorbic acid; the dispersant is acrylic acid (ester) / acrylamide copolymer and its derivatives, styrene / acrylic acid (ester) copolymer and its derivatives; the grinding method is sand milling; the sodium source is an inorganic sodium source and, the inorganic sodium source is sodium carbonate, sodium bicarbonate, and sodium hydroxide; the transition metal source is a manganese source, and the manganese source is manganese nitrate, manganese sulfate, and manganese carbonate; the anion source is an inorganic phosphorus source, and the inorganic phosphorus source is phosphoric acid, sodium phosphate and its acid salt.

[0041] S2. Drying of raw material powder: Drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder. Specifically, the drying method is flash drying.

[0042] S3, high temperature calcination of porous polyanion material: in a protective atmosphere, the precursor powder is calcined at high temperature, and after nucleation and crystallization, the porous polyanion material is obtained by natural cooling. Specifically, the sintering temperature is 800°C, the time is 12 hours; the protective atmosphere is a non-oxidizing atmosphere, and the non-oxidizing atmosphere is nitrogen, argon. S4, mixing of precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry. Specifically, the second carbon source is an inorganic carbon-containing compound carbon nanotube, carbon fiber, carbon black; the grinding method is sand grinding.

[0043] S5, drying of precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder. Specifically, the drying method is spray drying.

[0044] S6, high temperature secondary sintering: in a protective atmosphere, the dense precursor powder is subjected to high temperature secondary sintering, and a high-density polyanion material is obtained after natural cooling. Specifically, the sintering temperature is 800°C, the time is 12 hours, and the protective atmosphere is a non-oxidizing atmosphere, which is carbon dioxide, hydrogen, or helium.

[0045] Example 3 This embodiment relates to a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: Wet-mix and grind the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry. Specifically, the first carbon source is maltose, cyclodextrin, cellulose and its derivatives; the dispersant is maleic anhydride / α-olefin copolymer and its derivatives, maleic acid or its sodium salt / polyol allyl monoether polymer and its derivatives; the grinding method is ball milling; the sodium source is an organic sodium source, and the organic sodium source is sodium formate, sodium acetate, and sodium propionate; the transition metal source is a cobalt source, and the cobalt source is cobalt nitrate, cobalt sulfate, and cobalt hydroxide; the anion source is an organic phosphorus source, and the organic phosphorus source is hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylenephosphonic acid, and diethylenetriamine penta-methylenephosphonic acid.

[0046] S2. Drying of raw material powder: Drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder. Specifically, the drying method is high temperature pyrolysis drying.

[0047] S3, high temperature calcination of porous polyanion material: in a protective atmosphere, the precursor powder is calcined at high temperature, and after nucleation and crystallization, the temperature is naturally lowered to obtain a porous polyanion material. Specifically, the sintering temperature is 650°C, the time is 2 hours; the protective atmosphere is a non-oxidizing atmosphere, and the non-oxidizing atmosphere is nitrogen, hydrogen, or helium; S4, mixing of precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry. Specifically, the second carbon source is an inorganic carbon-containing compound such as graphene or flake graphite; the grinding method is ball milling.

[0048] S5. Drying of precursor powder: Drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder. Specifically, the drying method is flash drying or spray drying.

[0049] S6, high temperature secondary sintering: in a protective atmosphere, the dense precursor powder is subjected to high temperature secondary sintering, and after natural cooling, a high-density polyanion material is obtained. Specifically, the sintering temperature is 650°C, the time is 6 hours, and the protective atmosphere is a non-oxidizing atmosphere, which is hydrogen or helium.

[0050] Example 4 This embodiment relates to a preparation process of a high-density polyanion positive electrode material, comprising the following steps: S1. Mixing of raw material slurry: wet-mix and grind the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry. Specifically, the first carbon source is glucose, sucrose, starch, lactose, maltose, and cyclodextrin; the dispersant is maleic anhydride / styrene copolymer and its derivatives, maleic anhydride / α-olefin copolymer and its derivatives, maleic acid or its sodium salt / polyol allyl monoether polymer and its derivatives; the grinding method is sand milling; the sodium source is an inorganic sodium source, and the inorganic sodium source is sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium nitrate, and sodium oxalate; the transition metal source is a cobalt source and an iron source, and the cobalt source is cobalt nitrate, cobalt sulfate, and cobalt hydroxide, and the iron The sources are ferric sulfate, ferrous sulfate, ferric nitrate, ferric formate, ferric acetate, ferric / ferrous hydroxide, and ferrous oxalate; the anion sources are inorganic phosphorus sources and organic phosphorus sources, the inorganic phosphorus sources are phosphoric acid, sodium phosphate and its acid salts, sodium pyrophosphate and its acid salts, ammonium pyrophosphate and its acid salts, metaphosphoric acid, sodium metaphosphate and its acid salts, and sodium polyphosphate; the organic phosphorus sources are 2-phosphonobutane-1,2,4-tricarboxylic acid, polyaminopolyether-methylenephosphonic acid, 2-hydroxyphosphonoacetic acid, polyol phosphate, and bis-1,6-hexamethylenetriaminepenta(methylenephosphonic acid).

[0051] S2. Drying of raw material powder: Drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder. Specifically, the drying method is flash heating evaporation.

[0052] S3, high temperature calcination of porous polyanion material: in a protective atmosphere, the precursor powder is calcined at high temperature, and after nucleation and crystallization, the porous polyanion material is obtained by natural cooling. Specifically, the sintering temperature is 450-°C, the time is 20 hours; the protective atmosphere is a non-oxidizing atmosphere, and the non-oxidizing atmosphere is nitrogen or argon.

[0053] S4, mixing of precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry. Specifically, the second carbon source is an inorganic carbon-containing compound carbon nanotube, carbon fiber, carbon black; the grinding method is sand milling and ball milling.

[0054] S5, drying of precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder. Specifically, the drying method is spray drying.

[0055] S6, high temperature secondary sintering: in a protective atmosphere, the dense precursor powder is subjected to high temperature secondary sintering, and a high-density polyanion material is obtained after natural cooling. Specifically, the sintering temperature is 600°C, the time is 10 hours, and the protective atmosphere is a non-oxidizing atmosphere, which is carbon dioxide, hydrogen, or helium.

[0056] Application Example 1 High-pressure compaction of Na4Fe 2.91 Synthesis and Electrochemical Performance of (PO4)2P2O7 / C This embodiment involves high-pressure compaction of Na4Fe 2.91 (PO4)2P2O7 / C positive electrode material, the preparation method thereof comprises the following steps: Step 1: Sodium acetate, ferrous oxalate dihydrate, and phosphoric acid are added to water in a molar ratio of 4:2.91:4, and citric acid (the amount added is 0.12 times the molar amount of ferrous oxalate dihydrate) is added as a carbon source, and styrene (80%) / acrylic acid (20%) copolymer (the amount added is 0.03 times the molar amount of ferrous oxalate dihydrate) is added as a dispersant, and ground with a sand mill to form a uniform light yellow raw material slurry; Step 2: spray drying the raw material slurry at an air inlet temperature of 300°C and an air outlet temperature of 110°C to remove water from the solution and obtain a dry raw material powder; Step 3: In a nitrogen atmosphere, the precursor powder is calcined at 600°C for 10 hours to remove volatile components. After nucleation and crystallization, the temperature is naturally lowered to obtain porous Na4Fe 2.91 (PO4)2P2O7 / C materials; Step 4: Porous Na4Fe 2.91 (PO4)2P2O7 / C material and graphene (the addition amount is 0.2% of the porous material) are mixed with water and ground with a sand mill to form a uniform precursor slurry; Step 5: spray drying the precursor slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to achieve solid-liquid separation to obtain a dry and dense precursor powder; Step 6: Sinter the dense precursor powder at 600°C for 5 hours in a nitrogen atmosphere to further shrink the particles. After natural cooling, high-density Na4Fe 2.91 (PO4)2P2O7 / C material.

[0057] Highly compacted Na4Fe 2.91After (PO4)2P2O7 / C, SurP, and PVDF5130 were mixed and homogenized in a mass ratio of 9.4:0.3:0.3, the viscosity of the slurry was lower than 2600Pa.S, and the fluidity was good, indicating that the material had low porosity and high density, and had low adsorption capacity for binders and solvents during the homogenization process, which was beneficial to the subsequent coating process and improving the uniformity of the electrode surface loading. After that, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button battery in a glove box.

[0058] Figure 1 Highly compacted Na4Fe 2.91 The SEM image of (PO4)2P2O7 / C material shows that its surface is relatively dense with almost no obvious pores. The material is composed of primary particles of about 100nm interlocking with each other. Compared with Comparative Example 1 ( Figure 2 ), the material is sintered after secondary processing, and the pores between the particles are destroyed during the secondary grinding process. At the same time, since no volatile gas is generated during the secondary sintering process, the interfaces between the particles are melted and embedded with each other, forming a relatively dense internal structure. Due to the low porosity of this material, it exhibits a higher compaction density of about 2.35g / cm 3 , compared with 1.95 g / cm in Comparative Example 1 3 As for the compaction density, it increased by about 20.05%, indicating that after secondary shaping and sintering, the material has fewer particle gaps, a higher filling rate and a greater compaction density.

[0059] Table 1 shows that high-density Na4Fe 2.91The reversible discharge capacity of the (PO4)2P2O7 / C electrode at a rate of 0.1C (1C=129mAh / g) is 122mAh / g, which is slightly higher than 116mAh / g in Comparative Example 1, indicating that during the secondary grinding and sintering process, the uniformity between the elements is improved, which in turn leads to a corresponding increase in the crystallinity and phase purity of the material, and ultimately improves the discharge capacity of the material. The rate performance test results in Table 1 show that the capacity of the material at a rate of 10C is 98.5% compared to 0.1C, showing excellent rate performance, which is better than the porous material in Comparative Example 1, indicating that after the secondary grinding and sintering of the material, the dense contact between the particles greatly increases the electron transfer sites, which is beneficial to improve the electronic conductivity, thereby improving the rate performance of the material. In addition, Table 1 shows that the capacity retention rate of the electrode after 1000 cycles is as high as 99.8%, showing excellent cycle stability. Compared with Comparative Example 1 (96.2%), the higher capacity retention rate of this electrode is due to its dense particles, low porosity, small contact area with the electrolyte, and low interfacial side reactions, which in turn increases its structural stability during long cycles.

[0060] Application Example 2 Synthesis and Electrochemical Performance of Highly Compacted Na2FeP2O7 / C This embodiment relates to a high-pressure compacted Na2FeP2O7 / C positive electrode material, and its preparation method comprises the following steps: Step 1: Sodium carbonate, anhydrous ferric phosphate and phosphoric acid are added to water in a molar ratio of 1:1:1, and sucrose (the added amount is 0.10 times the molar amount of anhydrous ferric phosphate) is added as a carbon source, and a maleic acid (50%) / acrylic acid (50%) copolymer (the added amount is 0.05 times the molar amount of anhydrous ferric phosphate) is added as a dispersant, and ground with a sand mill to form a uniform light red raw material slurry; Step 2: spray drying the precursor slurry at an air inlet temperature of 280°C and an air outlet temperature of 80°C to remove water from the solution and obtain a dry raw material powder; Step 3: In an argon atmosphere, the precursor powder is calcined at 520°C for 15 hours to remove volatile components, and the porous Na2FeP2O7 / C material is obtained by naturally cooling after nucleation and crystallization; Step 4: Mix the porous Na2FeP2O7 / C material and carbon nanotubes (the amount added is 0.12% of the porous material) with water, and grind them with a sand mill to form a uniform precursor slurry; Step 5: spray drying the precursor slurry at an air inlet temperature of 200°C and an air outlet temperature of 70°C to achieve solid-liquid separation to obtain a dry and dense precursor powder; Step 6: In a nitrogen atmosphere, the dense precursor powder is sintered at 520°C for 15 hours to further shrink the particles, and a highly compacted Na2FeP2O7 / C material is obtained after natural cooling.

[0061] After the high-compacted Na2FeP2O7 / C, SurP, and PVDF5130 were mixed and homogenized in a mass ratio of 9.4:0.3:0.3, the viscosity of the slurry was lower than 2900Pa.S, showing good fluidity, small fineness, and fast screening rate, indicating that after the material was subjected to secondary grinding and calcination, the porosity between the material particles decreased, the penetration of the binder inside the particles decreased, and the slurry processing performance was significantly improved. After that, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum drying oven at 100℃ for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.

[0062] Table 1 shows that the compacted density of the material is as high as 2.39 g / cm 3 , much higher than 2.01 g / cm in Comparative Example 2 3 The compaction density shows that after the material is ground and granulated twice, its particles are in close contact, the pores are reduced, the particles are bonded to each other, the degree of densification is increased, and the compaction density is significantly improved. Table 1 shows that the reversible discharge capacity of the high-density Na2FeP2O7 / C electrode at a rate of 0.1C (1C=129mAh / g) is 115mAh / g, which is higher than 108mAh / g in Comparative Example 2, indicating that after the precursor powder is ground twice, the mixing uniformity between the elements is further increased, which is conducive to the formation of high-purity phases and high-crystallinity materials, thereby improving its discharge capacity to a certain extent. The rate performance test results in Table 1 show that at a rate of 10C, the capacity retention rate of the material is 97.8% compared to 0.1C, which is better than the porous material in Comparative Example 2, showing excellent rate performance, indicating that after the material is ground and sintered twice, the close contact between the particles improves the internal electronic conductivity of the material, reduces the interface internal resistance of the material, and significantly improves the rate performance of the material. In addition, Table 1 shows that after 1000 cycles, the capacity retention rate of the electrode is 99.5%, with almost no attenuation, showing excellent cycle stability. Compared with Comparative Example 2 (97.1%), the higher capacity retention rate of the electrode is due to its lower porosity and reduced electrolyte side reactions, which in turn increases its structural stability during long cycles.

[0063] Comparative Example 1 Na4Fe 2.91 Synthesis and Electrochemical Performance of (PO4)2P2O7 / C This embodiment involves Na4Fe 2.91 (PO4)2P2O7 / C positive electrode material, the preparation method thereof comprises the following steps: Step 1: Sodium acetate, ferrous oxalate dihydrate, and phosphoric acid are added to water in a molar ratio of 4:2.91:4, and citric acid (the amount added is 0.12 times the molar amount of ferrous oxalate dihydrate) is added as a carbon source, and styrene (80%) / acrylic acid (20%) copolymer (the amount added is 0.03 times the molar amount of ferrous oxalate dihydrate) is added as a dispersant, and ground with a sand mill to form a uniform light yellow precursor slurry; Step 2: spray drying the precursor slurry at an air inlet temperature of 300°C and an air outlet temperature of 110°C to remove water from the solution and obtain a dry precursor powder; Step 3: In a nitrogen atmosphere, the precursor powder was calcined at 600°C for 10 hours to remove the volatile components. After nucleation and crystallization, the temperature was naturally cooled to obtain porous Na4Fe 2.91 (PO4)2P2O7 / C material.

[0064] Na4Fe 2.91 After (PO4)2P2O7 / C, SurP, and PVDF5130 were mixed and homogenized in a mass ratio of 9.4:0.3:0.3, the viscosity of the slurry was higher than 28000Pa.S, the fluidity was poor, the viscosity was high, the uniformity of the coating process was extremely poor, and the surface density was uneven, indicating that the material had a high porosity. During the homogenization process, the binder easily penetrated into the material particles, resulting in excessive viscosity and difficult processing. After that, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum drying oven at 100℃ for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button battery in a glove box.

[0065] Figure 2 Na4Fe 2.91 The SEM image of (PO4)2P2O7 / C material shows that the primary particle size is about 100nm, and there is adhesion between particles, with a high porosity. This is mainly due to the pores formed by the volatile components produced during the pyrolysis of the raw materials. The presence of these pores will cause the powder material to become polished and the compaction density to decrease. Table 1 shows that the compaction density of this material is only 1.95g / cm 3 , which is lower than that of Application Example 1, indicating that the material has not been subjected to secondary grinding, crushing and calcination, and the pores in its particles are relatively large, and the compaction density will be reduced.

[0066] Table 1 shows that Na4Fe 2.91 The reversible discharge capacity of the (PO4)2P2O7 / C electrode at a rate of 0.1C (1C=129mAh / g) is 116mAh / g, which is slightly lower than that of Application Example 1, indicating that the mixing uniformity between the elements during the primary sintering process is low, and the phase purity and crystallinity of the material decrease during the sintering process, which ultimately leads to a decrease in its discharge capacity. The rate performance test results in Table 1 show that the capacity retention rate of the material at a rate of 10C is 91.2% compared to 0.1C, and the rate performance is poor. This is related to the presence of more pores in the material. The presence of pores reduces the contact between particles, reduces the electron transfer sites, and increases the internal resistance, which ultimately leads to a decrease in the rate performance of the material. In addition, Table 1 shows that the electrode has a capacity retention rate of 96.2% after 1000 cycles, and the cycle stability is lower than that of Application Example 1, indicating that the electrode particles have more pores inside, which increases the contact area with the electrolyte, increases the interface side reactions under high pressure, dissolves the interface elements during the cycle, and the interface CEI film continues to thicken, which leads to a decrease in its cycle stability.

[0067] Comparative Example 2 Synthesis and Electrochemical Performance of Na2FeP2O7 / C This embodiment relates to a Na2FeP2O7 / C positive electrode material, and its preparation method comprises the following steps: Step 1: Sodium carbonate, anhydrous ferric phosphate and phosphoric acid are added to water in a molar ratio of 1:1:1, and sucrose (the amount added is 0.10 times the molar amount of anhydrous ferric phosphate) is added as a carbon source, and maleic acid (50%) / acrylic acid (50%) copolymer (the amount added is 0.05 times the molar amount of anhydrous ferric phosphate) is added as a dispersant, and ground with a sand mill to form a uniform light red precursor slurry; Step 2: spray drying the above precursor slurry, with an air inlet temperature of 280°C and an air outlet temperature of 80°C, to remove moisture from the solution and obtain a dry precursor powder; Step 3: In an argon atmosphere, the precursor powder is calcined at 520°C for 15 hours to remove volatile components. After nucleation and crystallization, the temperature is naturally lowered to obtain a porous Na2FeP2O7 / C material.

[0068] After Na2FeP2O7 / C, SurP, and PVDF5130 were mixed and homogenized in a mass ratio of 9.4:0.3:0.3, the viscosity of the slurry was higher than 41000Pa.S, the viscosity was extremely high, the fluidity was poor, the slurry was difficult to screen, and the viscosity of the slurry rebounded greatly during the static process, indicating that the higher the porosity of the material, the stronger its adsorption capacity for the binder and solvent in the slurry during the homogenization process, resulting in a larger slurry viscosity, which will eventually affect the preparation of the electrode and even interfere with its electrochemical performance. After that, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and the film was dried in a vacuum drying oven at 100℃ for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.

[0069] Table 1 shows that the compacted density of the material is only 2.01 g / cm 3 , which is much lower than that in Application Example 2, indicating that the material without secondary grinding and granulation has a higher particle porosity, and the integrity and sphericity of the particles are not good, resulting in a decrease in compaction density. Table 1 shows that the reversible discharge capacity of the Na2FeP2O7 / C electrode at a rate of 0.1C (1C=129mAh / g) is only 108mAh / g, slightly lower than that in Application Example 2. This may be related to the uneven mixing of elements during the first grinding and sintering, which can easily lead to a decrease in the phase purity of the material, a decrease in crystallinity, and a decrease in sodium storage sites, ultimately affecting the performance of its reversible capacity. The rate performance test results in Table 1 show that at a rate of 10C, the capacity retention rate of the material is 89.3% compared to 0.1C, and the rate performance is poor. On the one hand, this is related to the presence of more pores in the material. The presence of pores reduces the transmission of electrons inside the material particles and increases the internal resistance of the material. On the other hand, the uneven mixing of elements may increase the sodium ion diffusion energy barrier, ultimately resulting in a decrease in the rate performance of the material. In addition, Table 1 shows that the capacity retention rate of the electrode after 1000 cycles is 97.1%, which is slightly lower than that of Application Example 2, indicating that the higher the porosity of the material, the more continuous side reactions with the electrolyte under high voltage, resulting in dissolution of material interface elements or continuous consumption of the electrolyte, and continuous growth of the CEI film, which ultimately reduces its structural stability during long cycles.

[0070] Table 1 Performance test results The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A process for preparing a high-density polyanion positive electrode material, characterized in that The following steps are involved: S1. Mixing of raw material slurry: wet-mixing and grinding the sodium source, transition metal source, anion source, first carbon source and dispersant to form a uniform raw material slurry; S2. Drying the raw material powder: drying the raw material slurry to achieve solid-liquid separation to obtain dry raw material powder; S3. High-temperature calcination of porous polyanion materials: in a protective atmosphere, the precursor powder is calcined at a high temperature, and after nucleation and crystallization, the porous polyanion material is obtained by naturally cooling down; S4, mixing the precursor slurry: wet-mixing and grinding the porous polyanion material and the second carbon source to form a uniform precursor slurry; S5. Drying the precursor powder: drying the precursor slurry to achieve solid-liquid separation to obtain dry and dense precursor powder; S6. High-temperature secondary sintering: In a protective atmosphere, the dense precursor powder is subjected to high-temperature secondary sintering, and a high-density polyanion material is obtained after natural cooling.

2. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In step S1, the first carbon source is one or more of citric acid, tartaric acid, ascorbic acid, acrylic acid, glucose, sucrose, starch, lactose, maltose, cyclodextrin, cellulose and their derivatives; In step S4, the second carbon source is one or more of inorganic carbon-containing compounds such as carbon nanotubes, carbon fibers, carbon black, graphene, and flake graphite.

3. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In steps S3 and S6, the sintering temperature of high temperature calcination and high temperature secondary sintering is 450-800°C, and the time is 0.1-24H.

4. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In steps S3 and S6, the protective atmosphere is a non-oxidizing atmosphere, which is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium.

5. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In step S1, the dispersant is one or more of acrylic acid (ester) / acrylamide copolymers and their derivatives, styrene / acrylic acid (ester) copolymers and their derivatives, maleic acid (ester) / acrylic acid (ester) copolymers and their derivatives, maleic anhydride / styrene copolymers and their derivatives, maleic anhydride / α-olefin copolymers and their derivatives, maleic acid or its sodium salt / polyol allyl monoether polymers and their derivatives.

6. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In steps S1 and S4, the grinding method is sand milling and / or ball milling.

7. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In steps S2 and S5, the drying method is one or more of flash drying, spray drying, high temperature cracking drying, freeze drying, air drying, and heating evaporation.

8. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In step S1, the sodium source is an inorganic sodium source and / or an organic sodium source, the inorganic sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium nitrate, and sodium oxalate; the organic sodium source is one or more of sodium formate, sodium acetate, sodium propionate, sodium phenol, sodium ethanol, sodium ascorbate, sodium citrate, sodium gluconate, ethylenediaminetetraacetic acid, and their derivatives.

9. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In step S1, the transition metal source is one or more of a manganese source, a cobalt source, and an iron source; the manganese source is one or more of manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese element and its oxide, basic manganese oxide, manganese acetate, and manganese phosphate; the cobalt source is one or more of cobalt nitrate, cobalt sulfate, cobalt hydroxide, cobalt element and its oxide, cobalt oxalate, cobalt carbonate, cobalt acetate, and cobalt phosphate; the iron source is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferric formate, ferric acetate, ferric hydroxide / ferrous hydroxide, ferrous oxalate, ferric phosphate, iron element and its oxide.

10. The process for preparing the high-density polyanion positive electrode material according to claim 1, characterized in that: In step S1, the anion source is an inorganic phosphorus source and / or an organic phosphorus source, the inorganic phosphorus source is one or more of phosphoric acid, sodium phosphate and its acid salts, ammonium phosphate and its acid salts, pyrophosphoric acid, sodium pyrophosphate and its acid salts, ammonium pyrophosphate and its acid salts, metaphosphoric acid, sodium metaphosphate and its acid salts, and sodium polyphosphate; the organic phosphorus source is one or more of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, diethylenetriamine penta (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, polyaminopolyether methylene phosphonic acid, 2-hydroxyphosphonoacetic acid, polyol phosphate, and di-1,6-hexamethylene triamine penta (methylene phosphonic acid).